2020
DOI: 10.1016/j.jagp.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Qigong for the Prevention, Treatment, and Rehabilitation of COVID-19 Infection in Older Adults

Abstract: The elderly are at high risk of contracting respiratory infectious diseases, including COVID-19 infection. The recent pandemic has the potential to cause significant physical and mental damage in older adults. Similarly to other mind-body exercises in Traditional Chinese medicine, Qigong features regulation of breath rhythm and pattern, body movement and posture, and meditation. Given these traits, Qigong has the potential to play a role in the prevention, treatment, and rehabilitation of respiratory infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 28 publications
(27 reference statements)
2
70
0
1
Order By: Relevance
“…//www.health.harvard.edu/blog/try-tai-chi-to-improve-balance-avoid-falls-201208235198) and NHS (https://www.nhs.uk/live-well/exercise/guide-to-tai-chi/), attempt to guide people on how to use mind-body exercises. Qigong has the potential to play a role in the prevention, treatment, and rehabilitation of respiratory infections, such as COVID-19(139), and can help enhance the antibody responses to influenza vaccination in the older adults(140). Moderate-intensity Pilates exercise program can increase salivary flow rate and S-IgA secretion(141), and can improve both cognitive and functional abilities as well as balance in older women(142).…”
mentioning
confidence: 99%
“…//www.health.harvard.edu/blog/try-tai-chi-to-improve-balance-avoid-falls-201208235198) and NHS (https://www.nhs.uk/live-well/exercise/guide-to-tai-chi/), attempt to guide people on how to use mind-body exercises. Qigong has the potential to play a role in the prevention, treatment, and rehabilitation of respiratory infections, such as COVID-19(139), and can help enhance the antibody responses to influenza vaccination in the older adults(140). Moderate-intensity Pilates exercise program can increase salivary flow rate and S-IgA secretion(141), and can improve both cognitive and functional abilities as well as balance in older women(142).…”
mentioning
confidence: 99%
“…Feng et al completed an extensive literature search for Qigong to examine its potential in COVID-19 prevention and rehabilitation. 88 They reviewed data for effectiveness in hypertension, asthma, COPD, mood disorders, cognitive impairment, pain relief and muscle strength. They concluded that the efficacy of Qigong is based on 4 mechanisms: management of stress and emotion, strengthening respiratory muscles, reducing inflammation, and enhancing immune function.…”
Section: Qigongmentioning
confidence: 99%
“…Complementary and alternative therapy Mindfulness 34,42,44,46,51,57,65,75,80,86,118,121,139 (10.4) Breathing techniques 34,40,51,121 (3.2) Yoga 40,51,60 (2.4) Qigong 69 (0.8) 25,38,40,42,51,70,75,86 (6.4) WhatsApp/chat support groups 57,78,81,95,119,125,126 (5.6) Specific media recommendations 47,64,84,145 (3.…”
Section: Meta-analysismentioning
confidence: 99%